Syeikh Yusuf Almakasari: Karya dan Pemikirannya - Syahrial Syahrial (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2007)
Syeikh Yusuf was an ulama who is also known as hero fighting in the struggle for independece. Because of his great service, he was declared a national hero not only by the government of Indonesia but also by South African government. His thoughts regarding tasawuf are reflected in his works. A comprehensive research is needed on this important figure in order is reveal one part the intelectual history of our nation.